2020
DOI: 10.1021/acsearthspacechem.0c00144
|View full text |Cite
|
Sign up to set email alerts
|

Microanalysis of Primary Biological Particles from Model Grass over Its Life Cycle

Abstract: This review examines the detailed chemical insights that have been generated through 150 years of work worldwide on magnesium-based inorganic cements, with a focus on both scientific and patent literature. Magnesium carbonate, phosphate, silicate-hydrate, and oxysalt (both chloride and sulfate) cements are all assessed. Many such cements are ideally suited to specialist applications in precast construction, road repair, and other fields including nuclear waste immobilization. The majority of MgO-based cements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 175 publications
(315 reference statements)
0
10
0
Order By: Relevance
“…20 Studies have found a rise in accumulation mode particles during plant growth with approximately 60% of emitted particles attributed to PBAPs. 33 This suggests a correlation between the plant's life cycle and PBAP emissions. A unique property of PBAPs is that some of them (e.g., pollen and fungal spore) tend to disintegrate by releasing fine fragments through multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Studies have found a rise in accumulation mode particles during plant growth with approximately 60% of emitted particles attributed to PBAPs. 33 This suggests a correlation between the plant's life cycle and PBAP emissions. A unique property of PBAPs is that some of them (e.g., pollen and fungal spore) tend to disintegrate by releasing fine fragments through multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…via oxidative modifications . Studies have found a rise in accumulation mode particles during plant growth with approximately 60% of emitted particles attributed to PBAPs . This suggests a correlation between the plant’s life cycle and PBAP emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Three papers deal with atmospheric emissions of PBAPs from such diverse systems as the model grass Brachypodium distachyon (China et al), 1 agricultural corn and soybean fields (Tomlin et al), 2 and tree pollen (Rivas-Ubach et al). 3 China et al 1 reveal that compositional characteristics and types of emitted biological particles are highly variable at the different growth stages of B. distachyon. Tomlin et al 2 find that particle classes are consistent between corn and soybean harvesting periods and emphasize that seasonal harvesting of crops may play an important role in regional atmospheric dynamics.…”
mentioning
confidence: 99%
“…Primary biological aerosol particles (PBAPs) are directly released from diverse systems of the biosphere into the atmosphere, while secondary organic aerosol (SOA) formation occurs through oxidation of biogenic volatile organic compound (BVOC) emissions. Three papers deal with atmospheric emissions of PBAPs from such diverse systems as the model grass Brachypodium distachyon (China et al), agricultural corn and soybean fields (Tomlin et al), and tree pollen (Rivas-Ubach et al) . China et al reveal that compositional characteristics and types of emitted biological particles are highly variable at the different growth stages of B.…”
mentioning
confidence: 99%
See 1 more Smart Citation